CD4 + T cell immunity against cutaneous melanoma encompasses multifaceted MHC II-dependent responses - Bawden, Emma G; Wagner, Teagan; Schröder, Jan; Effern, Maike; Hinze, Daniel; Newland, Lewis; Attrill, Grace H; Lee, Ariane R; Engel, Sven; Freestone, David; de Lima Moreira, Marcela; Gressier, Elise; et al. (Science immunology, 2024)
Whereas CD4 T cells conventionally mediate antitumor immunity by providing help to CD8 T cells, recent clinical studies have implied an important role for cytotoxic CD4 T cells in cancer immunity. Using an orthotopic melanoma model, we provide a detailed account of antitumoral CD4 T cell responses and their regulation by major histocompatibility complex class II (MHC II) in the skin. Intravital imaging revealed prominent interactions of CD4 T cells with tumor debris-laden MHC II host antigen-presenting cells that accumulated around tumor cell nests, although direct recognition of MHC II melanoma cells alone could also promote CD4 T cell control. CD4 T cells stably suppressed or eradicated tumors even in the absence of other lymphocytes by using tumor necrosis factor-α and Fas ligand (FasL) but not perforin-mediated cytotoxicity. Interferon-γ was critical for protection, acting both directly on melanoma cells and via induction of nitric oxide synthase in myeloid cells. Our results illustrate multifaceted and context-specific aspects of MHC II-dependent CD4 T cell immunity against cutaneous melanoma, emphasizing modulation of this axis as a potential avenue for immunotherapies.